Let the patients smoke: a defence of a patient privilege. Issue 3 (September 1990) - Lavin, M
Abstract : I examine two kinds of arguments in favour of imposing restrictions on smoking by hospitalised psychiatric patients. First, I look at patient-centered arguments in favour of restrictions. These arguments focus on the benefits that patients will receive if their smoking is stopped or curtailed. Second, I examine arguments that seek to justify restrictions by citing the costs that smokers impose on others. Neither kind of argument justifies any meaningful restrictions on the smoking of hospitalised psychiatric patients.